Association between tear and blood glucose concentrations: Random intercept model adjusted with confounders in tear samples negative for occult blood. Issue 2 (30th August 2020) - Aihara, Masakazu; Kubota, Naoto; Minami, Takahiro; Shirakawa, Rika; Sakurai, Yoshitaka; Hayashi, Takanori; Iwamoto, Masahiko; Takamoto, Iseki; Kubota, Tetsuya; Suzuki, Ryo; Usami, Satoshi; Jinnouchi, Hideaki; et al.
Abstract: Aims/Introduction: To prevent diabetic complications, strict glucose control and frequent monitoring of blood glucose levels with invasive methods are necessary. We considered the monitoring of tear glucose levels might be a possible method for non‐invasive glucose monitoring. To develop tear glucose monitoring for clinical application, we investigated the precise correlation between the blood and tear glucose concentrations. Materials and Methods: A total of 10 participants and 20 participants with diabetes were admitted, and blood and tear samples were collected. Before statistical analysis, we eliminated tear samples contaminated with blood. We observed the daily blood and tear glucose dynamics, and carried out a random intercept model analysis to examine the association between the blood and tear glucose concentrations. Results: Tear occult blood tests showed that the tear glucose concentrations and their variation increased in both participants with and without diabetes as contamination of blood increased. In both participants with and without diabetes, fluctuations of the plasma glucose concentrations were observed depending on the timing of collection of the samples, and the dynamics of the tear glucose concentrations paralleled those of the plasma glucose concentrations. The random intercept model analysis showed a significant association between the plasma and tear glucose concentrations in participants with diabetes ( P < 0.001). This association still existed even after adjusting for the glycated hemoglobin levels and the prandial state ( P < 0.001). Conclusions: It is important to eliminate the tear samples contaminated with blood. Tear glucose monitoring might be a reliable and non‐invasive substitute method for monitoring the blood glucose concentrations for diabetes patients, irrespective of glycated hemoglobin levels and timing of sample collection. Abstract : It is important to eliminate the tear samples contaminated with blood. Tear glucose monitoring might be a reliable and non‐invasive substitute method for monitoring the blood glucose concentrations for diabetes patients, irrespective of glycated hemoglobin levels and the timing of sample collection.